Factors influencing the brand awareness towards Malaysian National News Agency (BERNAMA). “A case study in Wangsa Maju, Kuala Lumpur” / Nur Masturina Omar - Omar, Nur Masturina (2011)
The research tries to examine factors that can influence the brand awareness towards Malaysian National News Agency (BERNAMA), a case study in Wangsa Maju, Kuala Lumpur. The first factor that researcher try to find is advertising. Nowadays, advertising plays a high role especially to create the brand awareness. The second factor that researcher try to examine is brand trust on web. Brand trust on web is familiarity analysis when building the trusting brand relationship The development and maintenance of consumer brand trust on the Web is at the heart of companies’ marketing plans, especially in the face of highly competitive markets with increasing unpredictability and decreasing product. The researcher tries to examine whether brand trust on web can influence BERNAMA or not. For the last factor that researcher try to examine is corporate reputation. Corporate reputation includes basic components, such as the image and quality. Corporate reputation helps the companies to get good employees, attract consumers, and increase consumers’ loyalty, which may be implemented as a factor of competitive performance and useful in obtaining the capital. Without good reputation it is very difficult for a company to survive or to make progress. From this research we can see there is relationship between advertising, brand trust on web and corporate reputation, which are influencing the brand awareness towards BERNAMA